Pengaruh Model Pembelajaran Example Non Example Terhadap Pemahaman Konsep Matematika - Tegar Nando; Muhamad Tahir; Muhamad Turmuzi (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
The purpose of this study was to determine the effect of the Example Non Example learning model on understanding mathematical concepts in class IV SDN 1 Kawo Pujut District in the Academic Year 2022/2023. In this study using a quantitative approach and type of experimental research, in this study also used methods of observation, testing, and documentation. The test method is used to find out the understanding of mathematical concepts for class IV SDN 1 Kawo Pujut District for the 2022/2023 academic year. While the observation method and documentation are used to collect data about the condition of teachers and students in class IV SDN 1 Kawo Pujut District for the 2022/2023 academic year. Data analysis using t-test formula. The calculation results show that the value of tcount > ttable is 3.112 > 3.015, which means rejecting H0 and accepting H1, so it can be concluded that there is an effect of applying the Example Non Example Learning model on students' mathematics learning outcomes in class IV SDN 1 Kawo Pujut District, Academic Year 2022/2023